The Influence of Self-Efficacy and Learning Independence Againts The Outcomes of The Study Material on Ecosystem Biology High School Student of Grade X - Ervan Nurkholis; Mieke Miarsyah; Reni Indrayanti (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
In education word one of a serious problem is a high to low student learning outcomes. Good learning outcomes will be achieved when students have the self-efficacy and learning independence in overcoming learning difficulties which affect them. This research aims to find out and analyze the influence of self-efficacy and learning independence against the outcomes of the study of biology students. The research method used is ex pose facto 2x2 factorial design. The sample of this research is the grade X with number of 74 students. The instruments in this research are self-efficacy questioner, learning independence questioner and the outcomes study quesioner. Prerequisites testing conducted distributed normal data using Kolmogorov Smirnov and homogenous test using Bartlet test. Based on hypothesis testing, it was concluded that there is no influence of self-efficacy and learning independence against the outcomes of the study and there is influence between learning independence on student learning outcomes at Senior High School in Bekasi.Keywords: self-efficacy, learning independence, student learning outcomes, ex post facto